TAZ/WWTR1 mediates liver mesothelial–mesenchymal transition induced by stiff extracellular environment, TGF‐β1, and lysophosphatidic acid. Issue 5 (20th April 2022) - Lua, Ingrid; Balog, Steven; Asahina, Kinji
Abstract: Mesothelial cells cover the surface of the internal organs and the walls of body cavities, facilitating the movement between organs by secretion of a lubricating fluid. Upon injury, mesothelial cells undergo a mesothelial–mesenchymal transition (MMT) and give rise to myofibroblasts during organ fibrosis, including in the liver. Although transforming growth factor‐β1 (TGF‐β1) was shown to induce MMT, molecular and cellular mechanisms underlying MMT remain to be clarified. In the present study, we examined how the extracellular environment, soluble factors, and cell density control the phenotype of liver mesothelial cells by culturing them at different cell densities or on hydrogels of different stiffness. We found that TGF‐β1 does not fully induce MMT in mesothelial cells cultured at high cell density or in the absence of fetal bovine serum. Extracellular lysophosphatidic acid (LPA) synergistically induced MMT in the presence of TGF‐β1 in mesothelial cells. LPA induced nuclear localization of WW domain‐containing transcription regulator1 (WWTR1/TAZ) and knockdown of Taz, which suppressed LPA‐induced MMT. Mesothelial cells cultured on stiff hydrogels upregulated nuclear localization of TAZ and myofibroblastic differentiation. Knockdown of Taz suppressed MMT of mesothelial cells cultured on stiff hydrogels, but inhibition of TGF‐β1 signaling failed to suppress MMT. Our data indicate that TAZ mediates MMT induced by TGF‐β1, LPA, and a stiff matrix. The microenvironment of a stiff extracellular matrix is a strong inducer of MMT. Abstract : Mesothelial cells cover the surface of the visceral organs and parietal walls of the body cavities. Upon injury, mesothelial cells undergo mesothelial–mesenchymal transition (MMT) and give rise to myofibroblasts during organ fibrosis. In the present study, we found that TAZ mediates MMT induced by transforming growth factor‐β1 (TGF‐β1), lysophosphatidic acid (LPA), and a stiff matrix.